(untitled) (Nepalese Journal of Radiology, 2020)
Hirschprung’s disease (HD) is also called as aganglionic megacolon. The entity falls in the group of congenital motor disorders. The usual presentation is in the form of not passing of meconium, abdominal distension with or without vomiting. We present a 2-years old child who was brought with complaints of constipation and difficulty in passing stool. The child was evaluated radiologically by plain radiography, ultrasonography (USG) and barium enema and was diagnosed as a case of short segment type of Hirschsprung disease. The parents had been counselled and advised for pull-through surgery for the child. It is a dilemma for the paediatrician to confirm the diagnosis of Hirschprung’s disease until a radiologically confirmed diagnosis is made. Many cases are delayed for the treatment because of non-diagnosis or delayed diagnosis. The importance lies in the early diagnosis for further surgical management.